Metal Content Of Midrib Sap Flour Salak Tree (Tgps) As A Thickening Agent - Fajrin Harahap, Muharram; Amanda Lubis, Rafiqah; Nurmi, Aisyah; Erwin Harahap, Darmadi (Publisher Cv. Inara, 2023)
The food processing industry, whether related to livestock, agriculture, or fishery products, often requires thickening additives to improve product quality. Salak trees are found around the Southern Tapanuli area of North Sumatra, Indonesia. Previous research showed the Midrib Sap Flour Salak Tree (TGPS) has fairly good quality content as a natural thickening agent but has not reported the quality of TGPS in terms of heavy metal content. Here, a study was carried out to determine the heavy metal content of TGPS. This research was conducted in January-March 2022 in Southern Tapanuli. The analysis showed that the metal content in TGPS does not exceed the threshold required in Indonesian Standard SNI 7387-2009.